PEMBERDAYAAN SISWA SEBAGAI KADER KESEHATAN DALAM PROGRAM EDUKASI KESEHATAN REPRODUKSI REMAJA DI SMP SWASTA MEDAN - Nur Asnah Sitohang; Diah Lestari Nasution; Cut Adeya Adella (Jurnal Riset Hesti Medan, 2018)
Adolescent reproductive and sexuality health in Indonesia is still low, this can be seen from the many cases of pregnancy out of wedlock, violence during courtship and abortion with high-risk drugs. The understanding of adolescents about reproductive health is the provision of adolescents in healthy and responsible behavior. But not all teenagers get information about reproductive health. This limitation of knowledge and understanding can bring teenagers towards risky behavior. This is a lack of information about sexuality and reproduction. Cadres health has a big role in realizing the optimal level of community health. Community service is carried out in two (2) junior high schools, namely Dharma Pancasila Private Junior High School (260 students and 21 cadres trained) and Al-Fhatiyan Private Middle School Medan (199 students and cadres trained by 16 students). The method used is by: 1. counseling with material on adolescent reproductive health; 2. cadre training; 3. Cadre mentoring. Evaluation of program success: pre test and post test cadres and student participants. Based on the results of the questionnaires distributed to students, the majority of data was 13 years old (47.5%), male sex (54%), high school parents education (62%) and entrepreneurial work (96.6%). The results of the dependent test obtained data, average knowledge before health education 26.23 and after health education39.58. The mean difference is 13,349 and the standard deviation is 3,911 and 95% CI 13,707-12,990. Based on the results of statistical tests obtained P = 0.001, it can be concluded that there is an influence of adolescent reproductive health cadres on student knowledge. For attitudes obtained data on average attitudes before counseling 27.57 and after counseling 39.58. The mean difference is 13,349 and the standard deviation is 3,802 and 95% CI 12,362 - 11,664. P value = 0.001 it can be concluded that there is an influence of adolescent reproductive health cadres on student attitudes. This PKM activity is useful in increasing knowledge and attitudes towards adolescent reproductive health. With increased knowledge of the behavior of adolescents to risky sexual behavior, and if the attitudes of adolescents towards sexual behavior are good, it is expected that sexually well and adolescents are expected to be responsible for their reproductive healthKeywords: cadres, education, health, reproduction, adolescents